Indicadores de aprendizaje organizacional en grupos de investigación universitaria (2014)
One concern of universities that allocate research resources is how to measure their results beyond academic products. This paper proposes organizational learning as one important result of the research process. From research results, it is proposed that indicators and indexes can measure the learning process and facilitator conditions in research groups. The work was carried out with researchers of groups that are part of the Research System of the University of Cauca, in Colombia.